Peningkatan Kemampuan Motorik Kasar Anak Melalui Permainan Tradisional Leng-Kaleleng - Erdanelli Erdanelli; Nur Hazizah (RC-INSTITUT, 2020)
Gross motor is a body movement that uses large muscles, most or all members of the body, which are influenced by the child's age, body weight, and physical development. For example, the ability to sit, kick, run, or go up and downstairs. The purpose of this study is to improve children's gross motor skills through traditional leng-kaleleng games. This research is of classroom action research/CAR. The subjects in this study were group B4 with a total of 14 children. The study was conducted in two cycles, with each cycle having three meetings. The technique used in collecting data is observation and documentation as well as research results that are processed using percentage techniques. The results showed in the first cycle of three meetings with a percentage of 43%. In cycle II there were three meetings with a percentage of 86%. It was concluded that traditional leng-kaleleng games can improve children's gross motor skills in the kindergarten Bustanul Athfal Aisyiyah V Padang.